MENINGKATKAN KREATIVITAS MASYARAKAT MELALUI PENGOLAHAN JAGUNG PULUT (Zea Mays Ceratina) MENJADI PRODUK YANG INOVATIF SERTA PEMANFAATAN MEDIA SOSIAL SEBAGAI MEDIA PROMOSI DI DESA ILOPONU KECAMATAN TIBAWA KABUPATEN GORONTALO - Saleh, Yanti; Indriani, Ria; Mustafa, Ramlan; Bobihu, Ijhan; Cahyani, Nisa Dwi; Rahim, Nur Cindi; Mahmud, Sri Anggita; Lasena, Nurhayati; Pontoh, Moh Fais; Indriani, Lusi (Universitas Negeri Gorontalo, 2023)
Pulut corn is one of the food commodities that has economic value and has the potential to be developed. Iloponu village has considerable pulut corn producing potential. The harvest of pulut corn is only sold in wet and dry form, there is no processing to become a new product that can add creativity to the community and can add economic value to the people of Iloponu village. Based on the existing problems, it is necessary to have innovative product innovations as an effort to take advantage of the potential of superior commodities in Iloponu village. The purpose of this activity is to increase community creativity in producing processed pulut corn commodities that have high selling power and increase public interest in denying family income. This counseling and training was carried out at the Iloponu Village Hall in stages and involved villagers and members of MSMEs assisted by Iloponu village. The method used is the commodity development model, which is an approach that involves the community directly as a subject and object in the implementation of counseling and training activities for making products from pulut corn. The results obtained during this activity the community understands the great benefits of the pulut corn commodity and increases people's creativity in product processing and the importance of entrepreneurship.